2018
DOI: 10.1096/fj.201700182rrr
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine channel complex stabilizer compound S48168/ARM210 as a disease modifier in dystrophin‐deficientmdxmice: proof‐of‐concept study and independent validation of efficacy

Abstract: Muscle fibers lacking dystrophin undergo a long-term alteration of Ca2+ homeostasis, partially caused by a leaky Ca2+ release ryanodine (RyR) channel. S48168/ARM210, an RyR calcium release channel stabilizer (a Rycal compound), is expected to enhance the rebinding of calstabin to the RyR channel complex and possibly alleviate the pathologic Ca2+ leakage in dystrophin-deficient skeletal and cardiac muscle. This study systematically investigated the effect of S48168/ARM210 on the phenotype of mdx mice by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 64 publications
(108 reference statements)
4
65
0
1
Order By: Relevance
“…4a, b). These data indicate that the magnitude of length Changes in cytosolic calcium have been implicated in ECC-induced force loss of mdx muscle [11,12,37], and increasing SERCA1a activity or reducing RyR1 SR leak have been shown to ameliorate several dystrophic phenotypes [12,[37][38][39][40]. Here, we incubated mdx EDL muscles with small-molecule calcium modulators that were previously identified through high-throughput screening assays as activators of SERCA (DS-11966966 and CDN1163; Additional file 7: Figure S7, [41][42][43][44]) or inhibitors of RyR1 leak (Chloroxine and Myricetin, [45]).…”
Section: Sarcolemmal Damage Is Associated With the Muscle Length Chanmentioning
confidence: 79%
“…4a, b). These data indicate that the magnitude of length Changes in cytosolic calcium have been implicated in ECC-induced force loss of mdx muscle [11,12,37], and increasing SERCA1a activity or reducing RyR1 SR leak have been shown to ameliorate several dystrophic phenotypes [12,[37][38][39][40]. Here, we incubated mdx EDL muscles with small-molecule calcium modulators that were previously identified through high-throughput screening assays as activators of SERCA (DS-11966966 and CDN1163; Additional file 7: Figure S7, [41][42][43][44]) or inhibitors of RyR1 leak (Chloroxine and Myricetin, [45]).…”
Section: Sarcolemmal Damage Is Associated With the Muscle Length Chanmentioning
confidence: 79%
“…Treatment of mdx mice with Rycal S107 also significantly reduced arrhythmias [161]. Similar studies in skeletal muscle found RyR1 stabilization to improve muscle strength, exercise tolerance, and muscle histopathology [58,170]. Whether long-term treatment to stabilize RyR2 in the heart can lead to improved cardiac outcomes in DMD requires further investigation.…”
Section: Ryr2 Stabilizationmentioning
confidence: 84%
“…Mice were treated for 4 weeks, in parallel to the training period; the treatment started 1 day before the beginning of the training phase and lasted until the day of sacrifice for ex vivo experiments. Throughout the study, all mice were maintained on a controlled diet with a daily amount of chow of 4-5 g/mouse [33][34][35][36][37].…”
Section: Formulation Composition: Bcaas + Ala (Weight Ratio Of L-leu:mentioning
confidence: 99%
“…Exer 3/6, Columbus Instruments, Columbus, OH, USA) in order to mimic the physical activity sustained by a regular, amateur runner. The protocol was adapted from those available from previous studies conducted in our laboratory and in other laboratories, both in C57BL/6J mice [38,39] and in animal models of neuromuscular disorders [33,34,36,37,40,41]. The exercise training consisted of 45 min running sessions, 5 days/week for 4 weeks on the treadmill.…”
Section: Formulation Composition: Bcaas + Ala (Weight Ratio Of L-leu:mentioning
confidence: 99%